Development of modern accounting - Horbachenko, Anna; Klimova, Olena (My University, 2014)
A series of revelations concerning accounting firms' failure to detect or publicly challenge irregularities or fraud when auditing the finances of a number of corporations led Congress to establish (2002) the Public Company Accounting Oversight Board. The board is appointed by the Securities and Exchange Commission and has the power to register and regulate accountants and firms that act as auditors. It sets standards for audits and is responsible for reviewing audits and disciplining accountants and accounting firms.
Keywords: accountant; accounting firms; development; бухгалтерський облік; кафедра ділової іноземної мови та міжнародної комунікації